Comparison of Polarized Versus Other Types of Endurance Training Intensity Distribution on Athletes’ Endurance Performance: A Systematic Review with Meta-analysis - Silva Oliveira, Pedro; Boppre, Giorjines; Fonseca, Hélder (Sports medicine (Auckland), 2024)
Background Polarized training intensity distribution (POL) was recently suggested to be superior to other training intensity distribution (TID) regimens for endurance performance improvement. Objective We aimed to systematically review and meta-analyze evidence comparing POL to other TIDs on endurance performance. Methods PRISMA guidelines were followed. The protocol was registered at PROSPERO (CRD42022365117). PubMed, Scopus, and Web of Science were searched up to 20 October 2022 for studies in adults and young adults for ≥ 4 weeks comparing POL with other TID interventions regarding V O 2 peak, time-trial (TT), time to exhaustion (TTE) or speed or power at the second ventilatory or lactate threshold (V/P at VT 2 /LT 2 ). Risk of bias was assessed with RoB-2 and ROBINS-I. Certainty of evidence was assessed with GRADE. Results were analyzed by random effects meta-analysis using standardized mean differences. Results Seventeen studies met the inclusion criteria ( n = 437 subjects). Pooled effect estimates suggest POL superiority for improving V O 2 peak (SMD = 0.24 [95% CI 0.01, 0.48]; z = 2.02 ( p = 0.040); 11 studies, n = 284; I 2 = 0%; high certainty of evidence). Superiority, however, only occurred in shorter interventions (< 12 weeks) (SMD = 0.40 [95% CI 0.08, 0.71; z = 2.49 ( p = 0.01); n = 163; I 2 = 0%) and for highly trained athletes (SMD = 0.46 [95% CI 0.10, 0.82]; z = 2.51 ( p = 0.01); n = 125; I 2 = 0%). The remaining endurance performance surrogates were similarly affected by POL and other TIDs: TT (SMD = – 0.01 [95% CI -0.28, 0.25]; z =  − 0.10 ( p = 0.92); n = 221; I 2 = 0%), TTE (SMD = 0.30 [95% CI – 0.20, 0.79]; z = 1.18 ( p = 0.24); n = 66; I 2 = 0%) and V/P VT 2 /LT 2 (SMD = 0.04 [95% CI -0.21, 0.29]; z = 0.32 ( p = 0.75); n = 253; I 2 = 0%). Risk of bias for randomized controlled trials was rated as of some concern and for non-randomized controlled trials as low risk of bias (two studies) and some concerns (one study). Conclusions POL is superior to other TIDs for improving V O 2 peak, particularly in shorter duration interventions and highly trained athletes. However, the effect of POL was similar to that of other TIDs on the remaining surrogates of endurance performance. The results suggest that POL more effectively improves aerobic power but is similar to other TIDs for improving aerobic capacity.